2023
DOI: 10.1111/jopr.13668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new support design on the marginal and internal gap of additively manufactured interim crowns using direct light deposition technology

Abstract: PurposeTo investigate the design and location of supporting structures on the marginal and internal gap of interim restorations.Materials and methodsA mandibular right first molar resin tooth was prepared for a full coverage crown and scanned using a laboratory scanner (3Shape D900). The scanned data were converted into standard tessellation language (STL) format and an indirect prosthesis was designed using computer‐aided design (CAD) software (exocad DentalCAD). The STL file was used to fabricate a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…65 Alharbi et al compared the marginal and internal gaps of milled and 3D-printed interim crowns and reported smaller gaps for 3D-printed interim restorations than milled crowns 66 ; however, other studies had conflicting outcomes. 53,67 The outcome of the current study showed that the marginal gaps of the ML and BL groups were within an acceptable range for definitive crowns 50,64 and comparable with previous studies; 53,[66][67][68] the solid group showed a high marginal gap of 318 mm. In addition, the mean internal gap of SC in the current study was significantly (p < 0.05) higher than that of the crowns with graded structures.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…65 Alharbi et al compared the marginal and internal gaps of milled and 3D-printed interim crowns and reported smaller gaps for 3D-printed interim restorations than milled crowns 66 ; however, other studies had conflicting outcomes. 53,67 The outcome of the current study showed that the marginal gaps of the ML and BL groups were within an acceptable range for definitive crowns 50,64 and comparable with previous studies; 53,[66][67][68] the solid group showed a high marginal gap of 318 mm. In addition, the mean internal gap of SC in the current study was significantly (p < 0.05) higher than that of the crowns with graded structures.…”
Section: Discussionsupporting
confidence: 87%
“…The sample size was selected based on similar previous studies [51][52][53] to achieve a power of 99%. A complete coverage restoration with a uniform thickness of 1.5 mm was designed on a mandibular first molar die with 50 mm die spacer, 0.5 mm from the margin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] Additionally, interim crowns manufactured through the DLS technique have demonstrated smaller marginal gaps compared to those produced via DLP and SM. 22 The fracture strength of interim prostheses holds paramount importance in ensuring their long-term functionality. Numerous studies have assessed the fracture load of interim crowns produced through both SM and AM.…”
mentioning
confidence: 99%